Worklife Balance: Social Dynamics of Work Life - Emergency Limatujuh; Mirwan Surya Perdhana (PT. Publikasiku Academic Solution, 2023)
Worklife balance is a phenomenon in the social dynamics of work life. Work balance is an important issue in increasing responsibility and balancing work, social and family activities. A company that is committed to creating a work balance that is most liked by employees and will get a good reputation. However, work and family conflict is a dual role for each individual, so work-life balance is important to ensure work effectiveness. Knowing the extent to which family scope can cause work conflicts, work can interfere with family life activities, family life can motivate employee performance and work activities can improve the quality of family life in PT employees. ASABRI (Persero) Semarang Branch. The type used in this research is qualitative through a case study approach to do so. The research method used to obtain data is interviews. Data analysis carried out qualitatively requires interactive activities starting from condensing data, presenting data and drawing conclusions that are carried out on an ongoing basis to meet all the required data. Work-life balance is related to physical and psychological meaning as stability between body and mind. A well-managed job is able to support work activities that can contribute to personal life. Employees who are given the opportunity to manage work life will actually help employees become more focused, productive, and efficient at work while being able to fulfill their personal needs, goals, and responsibilities. Personal life and work affairs are two different things and cannot be mixed up, but both are on the top priority scale that must be done.